Just between us - McElroy, David, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2018)
Just Between Us is a celebration of the vivid human connections that occur when traveling through some of the world's most stirring landscapes. These poems transport us from the Arctic to the tropics, over rural and urban lands, and even into the landscape of dreams. Throughout the verse is a sense of longing and the desire for intimacy, showing that despite our diverse lives, we are all driven to share our existences with one another.--Provided by publisher.
Woven Zigzag with Lightning. Cheyenne Mountain Zoo -- Cruising the Baltic -- Sabrina Bort -- Kriskindlmarkt -- Bellagio -- My First Wat -- Hulling Rice -- Waterfalls -- Prayer for the Love Coach -- Desert Walk -- Pachamama -- Chipa -- Seven Sleepers in the Street -- Volcanoes in the Window -- Zacualpa -- In Your Dreams. In Your Piano Tuner Dream -- In Your Apple Dream -- In Your Snowflake Dream -- In My Deli Dream -- In Your Goat Dream -- In Your Tango Dream -- In Your Sexual Fantasy Dream -- In Your Light Dream -- In Your Prison Guard Dream -- In Your Child Soldier Dream -- In Your Future Dream -- In Your Tie Dream -- In Your Retirement Dream -- I Got a Sawzall. Melting Pot -- Ice Road Trucker -- Paul Austin: Oilfield Pianist -- Videographer -- Intermission -- Weatherman Healing -- Take an Orange in Case You Get Lost -- Siping -- Distaff -- Encephalogram -- Florina Sings Die Loreley -- Three Weeks Rain -- I Got a Sawzall -- Against Indifference. Just Between Us -- Some Fogs -- Some Gossip -- Some Colors -- Some String -- Some Women's Hair -- Eclipse -- Dog Dancing -- Coccyx -- Pall Bearers -- So One Day -- Ugly Lovers -- Winter Garden -- Morning Paper.
Keywords: American poetry